PROTOTYPE ROTARY DRYER DENGAN BAHAN BAKAR BIOMASSA DITINJAU DARI PENGARUH VARIASI LAJU ALIR UDARA DAN DURASI WAKTU PENGERINGAN TERHADAP LAJU PENGERINGAN JAGUNG - Effendy, Sahrul; Syarif, Aida; Wardani, Deli Kusuma; Amalia, Indah (Politeknik Negeri Sriwijaya, 2019)
Rotary dryer are best suited for drying materials that are not easily broken and resistant to heat and require time for rapid drying. The drying process of corn kernels with rotary dryer by using biomass fuels becomes alternative to replace heat sources derived from the burning of fuel oil (BBM), as fuel prices tend to increase. While the availability of which decreased. The changed variable used is the air flow rate of the dryer air (3.5 m/s, 4 m/s, 4.5 m/s, 5 m/s and 5.5 m/s) and drying time (10 minutes, 15 minutes, 20 minutes, 25 minutes, and 30 minutes). The results showed that the moisture content of corn kernels was influenced by the drying air flow rate and the duration of drying time. The result of drying of corn kernels with the lowest water content is 9.66% achieved in the process conditions with drying air temperature 60oC with the air flow rate of the dryer air 5.5 m/s. Meanwhile, the highest rate of drying is 0.00307 kg/second. In testing the variation of drying time, the results of drying corn kernels with the lowest water content are 2.2% achieved at 30 minutes drying time and the highest drying rate was achieved at 30 minutes drying time, which was 0.002448 kg/s.